Gender studies of self-assessment and yourself physical health first year students’ - Ivaskiene, Vida; Skyriene, Valentina; Cepelionene, Jurgita; Skyrius, Evaldas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of this study is to assess aspects of first year students’ (young man and young women) health and self-esteem. Zaborskis’ (1997) questionnaire was used for the study to assess subjectively students’ perception of their personal health. Self-assessment was analysed using Rosenberg’s (1965) self-esteem scale. The survey using an anonymous questionnaire was implemented in Kaunas during the classes in spring semester 2010. The study involved 249 first-year students (120 young man and 129 young women).First-year students young man assess their physical health is not much better than the students young women. Self-esteem most of the young men and young women the average, and the third - high. Gender differences are established only for three terms of ten self-assessment (p <0,05).